Coalescence of RAGE in Lipid Rafts in Response to Cytolethal Distending Toxin-Induced Inflammation - Lin, Hwai-Jeng; Jiang, Zhi-Pei; Lo, Horng-Ren; Feng, Chun-Lung; Chen, Chih-Jung; Yang, Chia-Yu; Huang, Mei-Zi; Wu, Hui-Yu; Chen, Yu-An; Chen, Yu; Chiu, Cheng-Hsun; Lai, Chih-Ho (Frontiers in Immunology, 2019)
The receptor for advanced glycation end products (RAGE) interacts with various molecules in the cell membrane to induce an inflammatory response. The cytolethal distending toxin (CDT) produced by Campylobacter jejuni contains three subunits: CdtA, CdtB, and CdtC. Amongst, CdtA and CdtC interact with membrane lipid rafts, by which CdtB enters the nucleus to induce pathogenesis. In this study, we first explored the relationships between RAGE, lipid rafts, and inflammation in gastrointestinal epithelial cells exposed to CDT. Our results showed that CDT activated the expression of RAGE and high mobility group box 1 (HMGB1), followed by the recruitment of RAGE into lipid rafts. In contrast, RAGE antagonist inhibited CDT-induced inflammation via the RAGE-HMGB1 axis. Disruption of lipid rafts decreased CDT-induced downstream signaling, which in turn attenuated the inflammatory response. Furthermore, in vivo studies revealed severe inflammation and upregulation of RAGE and IL-1β in the intestinal tissues of CDT-treated mice. These results demonstrate that mobilization of RAGE to lipid rafts plays a crucial role in CDT-induced inflammation.